ACNE AND INSULIN RESISTANCE: A SYSTEMATIC REVIEW - Fitriana, Ilma (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Acne is a skin disorder that is characterized by persistent inflammation and involves the folliculopilosebaceous unit. It has an impact on a sizeable portion of the general population. Acne affects a disproportionate number of females and teenagers, especially those between the ages of 15 and 24, who are most susceptible to the condition. In recent times, there has been seen to be a growing interest in the possible connection between acne and insulin resistance (IR). This attention has been seen, and it is appreciated. It would appear that IR has a strong connection to acne, which is a persistent skin condition that can lead to inflammation. Research has been conducted on a wide variety of etiopathological factors that have been associated with the progression of IR. It would appear that obesity is one of the most common. Additionally, it would appear that factors such as chronic inflammation, hypertriglyceridemia, low HDL serum concentration, mitochondrial dysfunction, gut microbiota, and the excess activity of antagonistic hormones such as cortisol, glucagon, and thyroid hormones all play a significant role in the development of this condition. We identified a linkage between insulin resistance and severe acne vulgaris, which was reported to have a positive link with insulin resistance. On the basis of these findings, it is a legitimate assumption to hypothesize that medications that are now utilized for the treatment of insulin resistance would also be helpful for the treatment of severe acne vulgaris.